Reflecting about a great book: Actor and witness. Half a century of a health worker - José Aurelio Díaz Quiñones; María Lina Valdés Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The book Actor and Witness. Half a century of a Health worker, from Dr.C. Francisco Rojas Ochoa is a text of the so-called indispensable for study and consultation of all those who work in the health sector in any of its fields, both in care, education and research. Structured in four parts and complementary pages with their corresponding chapters, in addition to the preamble and the prologue, this book synthesizes in an elegant way, with an entertaining speech and of solid scientificity, the historical evolution of the author from his childhood to the present times. The purpose of this paper is to present some reflections that are considered fundamental and that are related to the conceptions that support the content of the aforementioned text.